Cyberbullying in Social Media - Yudiarso, Ananta; Jesseline, Anastasia; Litmantoro, Stefani Lusia (Universitas Nusa Cendana, 2024)
Misuse of social media platforms, especially cyberbullying, is a problem in society. Cyberbullying is an act that is deliberately carried out by someone to embarrass, insult, threaten, or curse another person. The purpose of this study is to dig deeper into cyberbullying. This study uses a qualitative method by means of interviews. The results of this study describe the impact of cyberbullying from the perspective of the victim. Data from the victim's perspective suggests decreased self-confidence, difficulty in completing tasks, and increased stress. Support from the surrounding environment is needed to help victims recover and become motivated again in their daily activities.